Metformin inhibits migration and invasion of renal carcinoma cell line 786-O by regulating acetylation of histone - HE De-jiao; YANG Ding-ping; LIU Hong-yan; LI Hao-yong (Linchuang shenzangbing zazhi)
Objective To investigate the mechanism of metformin inhibition of migration and invasion of renal carcinoma cell line 786-O.Methods Transwell migration and Matrigel invasion assays were used to examine the role of metformin at 10 mM and 20 mM on migration and invasion of the cell line 786-O.Expression of E-cadherin,vimentin,MMP-2 and MMP-9 as well as acetylation of histone H3 K9,H4 K12 and H4 K16 were detected by western blotting after metformin treatment.When combining the histone acetyltransferase inhibitor C646 with metformin,effect of metformin regulation of histone acetylation on migration of the cell line 786-O was observed through Transwell assay.Results Both 10 mM and 20 mM metformin remarkably inhibited migration and invasion of 786-O cells(P<0.05).The expression of E-cadherin was upregulated while expression of vimentin,MMP-2 and MMP-9 was downregulated after exposure to metformin(P<0.05).What’s more,the acetylation levels of histone H3 K9、H4 K12 and H4 K16 were significantly upregulated by metformin treatment(P<0.05).Combination of metformin with C646 could blocked inhibition of migration resulting from metformin treatment alone(P<0.05).Conclusions Metformin inhibits migration and invasion of renal carcinoma cell line 786-O through upregulation of histone acetylation.